Maize- Peanut Intercropping Under Inoculated with Azotobacter chroococcum - Siavash Pourjani; Hashem Aminpanah; mohammadnaghi safarzade vishekaei (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
Intercropping and plant growth-promoting rhizobacteria improve sustainability of agro-ecosystems. To evaluate the effect of Azotobacter (Azotobacter chroococcum) inoculation on productivity of a peanut /maize intercropping system, a two-year study was design as a randomized complete block in a factorial arrangement with three replicates at Astaneh-ye Ashrafiyeh, Guilan province. Factors were Azotobacter inoculation [control (non-inoculated) and inoculated with Azotobacter chroococcum) and intercropping pattern (Sole cropping of peanut and maize, additive intercropping pattern at three levels (100% peanut + 100% maize, 100% peanut + 50% maize, and 50% peanut + 100% maize), and replacement intercropping pattern at three levels (50% peanut + 50% maize, 67% peanut +33% maize, and 33% peanut + 67% maize). Results showed that gain yields of maize and peanut were significantly affected by Azotobacter inoculation and intercropping pattern. Inoculation with Azotobacter chroococcum significantly increased grain yields of peanut and maize by 10% and 16%, respectively. Maximum and minimum of land equivalent ratio (LER) were observed at 100% peanut + 50% maize and 50% peanut + 50% maize, respectively and inoculated intercropped plots with Azotobacter chroococcum had 12-16% grater LER that non-inoculated ones. Regards to impossibility of mechanical weed control by machines in additive intercropping patterns, to obtain the highest productivity in maize/peanut intercropping system, intercropping pattern of 100% peanut + 50% maize along with Azotobacter application will be suitable in fields with low weed density. Otherwise, based on LER and grain yield of peanut, the intercropping pattern of 67% peanut + 33% maize along with Azotobacter application will be suitable.